Language and Culture - Kramsch, Claire (Oxford : University Press, 1998)
This bibliography contains 297 references to a variety of print-format materials about the Shuadit (Judeo-Provencal) culture and language. Included references are written in English, Dutch, French, German, Hungarian, Latin, Portuguese, Rumanian, Spanish, and Shuadit. Hebrew and Yiddish entries have been translated into English. Section 1 contains reference materials, while section 2 presents general works about the Shuadit language. Section 3 contains nine parts with entries in the specific fields of: (1) language; (2) literature; (3) poetry; (4) drama; (5) music; (6) religion; (7) biography; (8) economics, history, and sociology; and (9) science and medicine. An introduction describes a brief history of the development of this language and culture and the prominent writers in the field. An author index is included. (JHP)
Microfiche.
Keywords: Culture; Jews; Judaism; Languages; Reference Materials; Religious Cultural Groups; Resource Materials; Social Studies; Jewish Languages -- Shuadit; Jewish Studies -- Provencal; Reference Materials, Bibliographies